Improving pork burgers quality using Zingiber officinale Roscoe powder (ginger). (July 2017) - Mancini, Simone; Paci, Gisella; Fratini, Filippo; Torracca, Beatrice; Nuvoloni, Roberta; Dal Bosco, Alessandro; Roscini, Valentina; Preziuso, Giovanna
Abstract: Pork burgers were evaluated for physical-chemical characteristics, fatty acids profile, lipid oxidation, antioxidant capacity, microbiological growth and sensory evaluation during storage time of seven days at 4 °C as function of three formulations as only meat (control, B) and meat added with ginger powder at the percentage of 1 and 2% (BG1 and BG2). BG1 and BG2 were less redness than control ones with incremented yellow hue. These modifications in color parameters did not modify sensory characteristics of burgers. PUFA were incremented (both PUFAω3 and PUFAω6) by the addition of ginger. Furthermore, BG1 and BG2 burgers showed to be less sensitive to lipid oxidation and to possess an increase in antioxidant capacity. Microbial growth evaluation of total aerobic count and Pseudomonas spp. showed that ginger powder delayed in time the bacterial contamination. Results highlighted that the presence of ginger led to an enhanced shelf life and health characteristics of burgers (increasing peroxidisability, ratio hypocholesterolemic/hypercholesterolemic and ratio ω3/ω6; reducing atherogenicity and thrombogenicity). Highlights: PUFAω3 and PUFAω6 content increased by addition of ginger powder to pork burgers. Ginger powder delayed lipid oxidation and microbial growth. Burgers added with ginger powder showed an increased antioxidant capacity.